Advocacy Corner: The Value of Middle Grades Licensure on K-12 Mathematics Achievement (pp. 31–36) - Roberts, Thomas; Pachnowski, Lynne (Ohio Journal of School Mathematics, 2020)
The authors provide an overview of teacher licensure with a focus on the importance of middle grades licensure. Given the recent trend in reorganizing schools to serve more grade bands, there isconcern that Ohio will move to re-implement a K-8 teaching license. The authors address this issue and provide recommendations to policy makers, teacher preparation programs, and school administrators to help maintain mathematics achievement in Grades 4–12.